Synthesis, characterisation and stability of superparamagnetic maghemite nanoparticle suspension. (8th December 2014) - Nurdin, I.; Johan, M. R.; Yaacob, I. I.; Ang, B. C.; Andriyana, A.
<x content-type="archive" xml:space="preserve">Abstract</x> Maghemite nanoparticles were synthesised using the co-precipitation method and characterised by various techniques, including X-ray diffraction, transmission electron microscopy, alternating gradient magnetometry, dynamic light scattering and zeta potential. The stability of the suspension was monitored by measuring the particle size distribution and zeta potential using dynamic light scattering over a period of few months. The pattern obtained from X-ray diffraction confirmed that the particles were maghemite with crystallite size of 9·4 nm. Transmission electron microscopy observations and analyses showed that the mean physical size of the nanoparticles was 9·5 nm. The nanoparticles show superparamagnetic behaviour with magnetisation value at ±10 kOe of 32·18 emu g−1. The intensity averaged particle size of as-synthesised maghemite nanoparticles was 45·3 nm. The suspension was stored for periods of 2, 4 and 8 months. The intensity averaged sizes were 47·1, 50·5 and 52·1 nm respectively. No sedimentation was observed. The suspension's zeta potential value was 44·6 mV for as-synthesised sample and 43·3, 42·7 and 41·8 mV for sample after storage period of 2, 4 and 8 months, respectively. This indicated that the suspension was very stable.